Impact of Food Beverage Price Index and Exchange Rate Volatility on Economic Growth - Olanrewaju k, Onasanya; Emmanuel, Adeniji Oyebimpe (International Journal of Business, Economics and Management, 2014)
Many factors such as money supply, exchange rate, interest rate, gross domestic product, inflation rate, unemployment rate, frictional unemployment and other flow variables have great impact on economic growth rate. These factors have significant effect on capital movement, business outlook and economic development. Over past decades, numerous studies have used these variables to investigate their impact on economic growth especially using the econometric approach. Results obtained from such studies have motivated further research. However, this research seeks to address the impact of food, beverage price index and exchange rate volatility on economic growth using annual time series data for the period: 1980 to 2010. The research entailed the use of three different unit root test techniques, Engle Granger step procedure for cointegration test, vector error correction mechanism, variance decomposition, Johansen trace test, impulse response function, Engle Granger causality test and vector auto regression. The research findings reveal that Argumented Dickey Fuller test method was the best method to identify Stationarity at 2nd difference i.e. I (2). A long run relationship was found to exist among the variables since the error of the cointegrating regression was stationary, and a singleton of long run relationship was found based on the result obtained from Johansen trace test. An independent causality was observed among the variables i.e. lagged values of real exchange rate and food beverage price index do not correlate with the lagged values of real gross domestic product rate. Statistical and positive / negative relationships were observed for real exchange rate and food beverage price index respectively. Real exchange rate has a significant effect on real gross domestic product in both long and short runs while food beverage price index has a significant effect in short run but a slight effect on real gross domestic product in long run. Short run disequilibrium was exhibited by vector error correction indicating that at about 90.1% the error will be corrected in the next period which shows that real gross domestic product will converge to its equilibrium when there is a sudden change or shock between real exchange rate and food, beverage price index.